Adding a purple corn extract in rats supplemented with chia oil decreases gene expression of SREBP-1c and retains Δ5 and Δ6 hepatic desaturase activity, unmodified the hepatic lipid profile. (May 2018) - Reyna Gallegos, Sixto; Torres Arrunátegui, Génesis; Valenzuela, Rodrigo; Rincón-Cervera, Miguel Ángel; Villanueva Espinoza, María Elena
Highlights: Chia oil is a source of α-linolenic acid, the purple corn of anthocyanins. Chia oil supplementation increases the expression of PPAR-α. Dietary intake of purple corn extract (PCE) decreases the expression of SREBP-1. Expression of Δ5D increases with chia oil and decreases with PCE; Δ6D is refractory to these factors. A high dose of chia oil reduces the enzymatic activity of Δ5D and Δ6D, but PCE retains activity. Abstract: Flavonoids upregulate gene expression of PPAR-α and underregulate the gene expression of SREBP-1c, and their intake increases the plasmatic concentration of n-3 LC-PUFAs. However, the biological mechanisms underlying these effects have not been elucidated. In this work, the effect of oral supplementation of ALA from chia ( Salvia hispanica L .) seed oil and anthocyanins from a purple corn extract (PCE) on gene expression of SREBP-1c, PPAR-α and Δ5 and Δ6 desaturases (Δ5D and Δ6D), the activity of these enzymes in the liver as well as the hepatic lipid profile were evaluated in thirty-six female Sprague Dawley rats whose diet was supplemented with olive oil (OL), chia oil (CH), olive oil and PCE (OL + PCE) or chia oil and PCE (CH + PCE). Gene expression of PPAR-α was significantly higher when supplemented with CH and CH + PCE, SREBP-1c gene expression was higher when supplemented with chia oil. CH supplementation enhanced Δ5D expression whereas no significant differences between treatments were observed concerning Δ6D gene expression. Activities of both desaturases were increased by including olive oil (OL + PCE and OL), and they were found to be higher in CH + PCE respect to CH for both enzymes. The ALA and n-3 LCPUFAs hepatic content was higher with CH, decreasing the levels of AA and n-6 LCPUFAs. It is concluded that the joint action of flavonoids such as anthocyanins and ALA show an anti-adipogenic effect. Desaturase activity was inhibited by ALA and kept by the anthocyanins from PCE, thus anthocyanins would exert a protective effect on the desaturase activity but they would not affect on its gene expression, however, high doses of ALA increased the production of its metabolites, masking the effect of PCE.